From Outsider to Outsider: A Study of Iranian Baha’ís’ Identity in Iran and the United States - Naghme Naseri Morlock (Journal of Hate Studies, 2023)
Negotiating one’s identity is a complex process that becomes complicated when a person is ascribed an outsider status because of any one identity. Iranian Baha’ís are a significantly understudied population who experience an outsider status, both in their home country where they are persecuted due to animus towards them by the government and religious leaders, and in the United States. They are persecuted in a range of ways, including through denial of education, name-calling, harassment, torture, and killing. Using data from 50 in-depth interviews with first-generation Iranian Baha’í immigrants, I discuss their experience of the denial of a national identity, the importance of their religious identity, and their development of a collective Baha’í identity in Iran. Then I explore their experiences in the United States, including navigating cultural differences between Baha’í immigrants and American Baha’ís, spiritual differences across countries, and differences in life experiences. The Baha’í immigrants’ narratives and experiences reaffirm and complicate our understandings of how religious, national, and cultural identities are negotiated.